Validity of Interactive Learning Media Integrated Critical and Creative Thinking Skills Aided by the Lectora Inspire Application - Silvi Yulia Sari; Atifah Hirahmah; Hidayati Hidayati; Fanny Rahmatina Rahim (Universitas Lambung Mangkurat, 2023)
The importance of the ability to think critically and creatively in the learning process, especially in physics, is a challenge for educators to continue to improve the quality of learning, both in implementing the learning process and developing appropriate learning resources. This study aims to develop valid interactive learning media with the help of the Lectora Inspire application to improve the critical and creative thinking skills of high school students, especially in straight and parabolic motion material. The research design used the ADDIE model, including the stages of analysis, design, development, implementation, and evaluation. This research is being developed through validation activities from three validators from the Padang State University physics department. The instrument for collecting data was an interactive learning media assessment sheet validated by experts. The subjects of this study were experts from the physics department lecturer Padang State University. The data analysis technique used Aiken's validity index. The validation results of learning media product development are in a very valid category, with an average value of 0.816. This indicates that interactive learning media that integrates critical and creative thinking skills with the help of the Lectora Inspire application have a very valid category. This validity component shows the feasibility of the product in material substance, audio-visual communication display, learning design, software utilization, assessment of critical thinking skills, and assessment of creative thinking skills.